Investigating the Epidemiology of Trauma in Children Under the Age of 15 Years in Semnan Province, Iran, From 2014 to 2018 - Nilufar Safaie; Mohammadreza Moonesan; Majid Mirmohammadkhani; Elnaz Haidar; Kamyar Mansori (علوم بهداشتی ایران)
Background and Purpose: Trauma is one of the main causes of mortality and morbidity in children. This study examines the epidemiology of trauma in children under the age of 15 years in Semnan Province in Iran from 2014 to 2018. Materials and Methods: This retrospective study was conducted on 2218 traumatized children who were referred to the emergency department of Kowsar Semnan Hospital from 2014 to 2018. The study was conducted as a census. The data included demographic and clinical variables, extracted from the medical records department of Kowsar Hospital in Semnan from 2014 to 2018. The data were analyzed using the SPSS software, version 26. Meanwhile, the P<0.05 was considered a significant level. Results: A total of 2218 injured children were examined, of which 55.9% were boys. Most of the participants were in the age group of 10-15 years. The Mean±SD of hospitalization days in the general ward and the intensive care unit were 33.1±13.2 and 11.2±0.39 days, respectively. The most common site of injury was the upper limbs (54.4%). The home was the most frequent place of occurrence of accidents leading to trauma (40.7%). Most of the children’s traumas occurred in the summer season (53.4%). The most common event leading to trauma was falling (48.8%) and 0.4% died. In addition, a statistically significant relationship was observed between the cause of trauma and age (P<0.05). Conclusion: The most common places of trauma were related to the house and the street due to falls and accidents; therefore, it is necessary to inform families of the dangers for children and pay attention to various measures, such as securing homes and teaching children traffic rules and regulations.